Non‐pesticide alternatives for reducing feeding damage caused by the large pine weevil (Hylobius abietis L.). (5th May 2020) - Lalík, Michal; Galko, Juraj; Nikolov, Christo; Rell, Slavomír; Kunca, Andrej; Modlinger, Roman; Holuša, Jaroslav
Abstract: The large pine weevil ( Hylobius abietis L.) is an important pest of young forest stands in Europe. Larvae develop under the bark of freshly cut pine and spruce stumps, but maturing weevils feed on the bark of coniferous seedlings. Such seedlings frequently die because of bark consumption near the root collar. We tested the effect of three treatments (the insecticide alpha cypermethrin, a wax coating and a glue coating) on the feeding damage caused by H. abietis on Douglas fir ( Pseudotsuga menziesii ) and Norway spruce ( Picea abies ) seedlings under semi‐natural conditions. In two experiments (one in 2016 and another in 2017) seedlings in cages were subjected to pine weevil feeding for 16 weeks under shaded outdoor conditions. The experiment in 2016 compared insecticide and wax treatments and an untreated control on Douglas fir and Norway spruce, and the experiment in 2017 compared insecticide, wax and glue treatments and an untreated control on Norway spruce. In both experiments, all treatments significantly reduced H. abietis feeding damage at week 8 at the end of both experiments (week 16); the effect of treatments was significant only on spruce seedlings. The damages on Douglas fir seedlings was less on treated seedlings than on untreated control seedlings but differences were not significant. Coating stems with glue and especially with wax was generally effective at reducing weevil damage and in most cases provided control that was not significantly different from that provided by insecticide treatment. Our results suggest that a wax coating has the potential to replace the protection of seedlings provided by insecticides. Abstract :